Coral reef growth pattern in eastern Brazil has not changed since the Holocene - Vasconcelos, Mayanne J. O.; Leão, Zelinda M.A.N.; Kikuchi, Ruy K.P. (Quaternary and Environmental Geosciences, 2018)
Lithocronological study of Holocene inshore reef sequences from eastern Brazil, recovered from drill holes and associated with surveys of modern reefs, allows the reconstruction of the growth pattern of reefs since their beginning in the Holocene and its comparison with present-day reefs. The interpretation of the growth pattern of the studied reefs reveals their evolution from a lithofacies of coral-algal bindstone/framestone that was deposited in a low-wave-energy environment to a lithofacies composed of coral rudstone up to a high-energy environment with accumulation of a coral framestone lithofacies. This pattern was mostly influenced by the wave energy regime, regional sea-level history and shallow antecedent reef substrate. Despite the stages of reef evolution not occurring synchronously over time, they did not exhibit any regional variation during their development. The coral fauna that built the reefs did not change much since the beginning of reef growth (approximately 7,000 yr BP), suggesting that the environmental conditions in this region have most likely remained favorable for the development of coral reefs. The coral fauna that built the Brazilian reefs is mostly composed of resistant and well-adapted endemic coral species, which biodiversity has remained constant throughout the development of the reefs